Exploring the oxidative, antimicrobial and genomic properties of Campylobacter jejuni strains isolated from poultry. (August 2018) - Ugarte-Ruiz, Maria; Domínguez, Lucas; Corcionivoschi, Nicolae; Wren, Brendan W.; Dorrell, Nick; Gundogdu, Ozan
Abstract: Campylobacter jejuni is the leading cause of food-borne bacterial enteritis in humans, with contaminated poultry products considered the main source of infection. To survive the food chain, C. jejuni utilizes multiple defense mechanisms that counter oxidative and aerobic stresses. In this study, we phenotypically characterised 63 C. jejuni strains with oxidative stress survival and antimicrobial susceptibility testing to investigate correlations between these two phenotypes against the source of the strains and the presence of the MarR regulators RrpA and RrpB which have a role in regulating the response to oxidative and aerobic stress. C. jejuni strains isolated from meat and neck skin displayed the highest resistance to oxidative stress. In addition, C. jejuni strains that have an rrpA + rrpB − profile exhibit increased resistance to oxidative stress and to antimicrobials. Here we establish a preliminary link between the distribution of RrpA and RrpB and the increased resistance to antimicrobials. This study provides insight into how the genotypic make up of C. jejuni can influence the ability of the bacterium to survive within areas of high oxygen stress, such as the food chain, and subsequently can have a potential negative impact on human health. Highlights: C. jejuni strains isolated from meat and neck skin displayed the highest resistance to oxidative stress. C. jejuni strains that have an rrpA + rrpB - profile exhibit increased resistance to oxidative stress and to antimicrobials Genotypic make up of C. jejuni can influence ability to survive within areas of high oxygen stress, such as the food chain